Analysis of human resource development in improving employee performance productivity Regional Financial and Asset Management Agency (BPKAD) Papua Province - Lani , Lusiana Riska; Hutajulu, Halomoan; Mollet , J. Ary (Global Academy of Business Studies, 2025)
Purpose: This study aims to analyse the development of human resources (HR) in improving employee performance productivity at the Regional Financial and Asset Management Agency (BPKAD) of Papua Province. Research methodology: This research uses a mixed-method approach: quantitatively through questionnaires distributed to 45 respondents, and qualitatively through in-depth interviews with BPKAD employees. Data were analysed using simple linear regression and supported by SWOT analysis. Results: The study found that HR development significantly influences the improvement of employee performance productivity. The simple linear regression analysis showed that the HR development variable (X) contributed 73.5% to the regional financial performance variable (Y), with a significance value of <0.001. Qualitative data revealed that training and technical guidance are the primary HR development strategies, despite challenges such as budget constraints, limited access to training, and a lack of field-specific experts. Conclusions: Planned HR development supported by training and continuous evaluation improves employee efficiency and accountability. Strategic HR improvement should focus on optimising internal strengths and leveraging external opportunities in a collaborative and sustainable way. Limitations: The study is limited by the small sample size (45 respondents) and potential constraints in qualitative generalisation due to context-specific findings at BPKAD Papua Province. Contribution: This research contributes to the literature on public sector HR development by highlighting the measurable impact of HR strategies on performance outcomes and identifying actionable improvement areas through SWOT-based analysis.